The Influence of Nanny Parenting on Sibling Rivalry in Early Childhood - Sasmita, Shafira Dita; Yudi Ferdiansyah; Meli Fauziah (Neo Journal of economy and social humanities, 2025)
This study aims to analyze the influence of non-parental care involvement, especially professional caregivers such as nannies, on the dynamics of sibling rivalry in early childhood. This study uses a qualitative approach with systematic literature review and digital ethnography methods to examine in-depth the experiences of families and children who are cared for by non-parental figures. Data were collected from international empirical studies published between 2014-2024, focusing on children aged 2-6 years. The results showed that the involvement of non- parental caregivers significantly influenced interaction patterns between siblings. Three patterns of involvement were found: intensive, moderate and minimal, each of which had a different impact on the frequency and form of rivalry between siblings. In intensive parenting patterns, the phenomenon of triangulated competition emerged where children compete not only for parental attention, but also emotional validation from caregivers. Meanwhile, good quality and integrated caregiver engagement can reduce conflict and improve children's social skills. The findings emphasize the importance of consistency, caregiver training, and parental emotional involvement in mitigating the negative impacts of non-parental care. This study makes a theoretical contribution through the application of symbolic-interactionism in explaining the negotiation of meaning and the formation of children's social identity in the context of modern families.